A Unique Informationally Efficient Allocation Mechanism in Economies with Consumption Externalities. - Tian, Guoqiang (International Economic Review, 2004)
This article investigates the informational requirements of resource allocation processes in pure exchange economies with consumption externalities. It is shown that the distributive Lindahl mechanism has a minimal informational size of the message space, and thus it is informationally the most efficient allocation process that is informationally decentralized and realizes Pareto-efficient allocations over the class of economies that include nonmalevolent economies. Furthermore, it is shown that the distributive Lindahl mechanism is the unique informationally efficient decentralized mechanism that realizes Pareto-efficient and individually rational allocations over a certain class of nonmalevolent economies. Reprinted by permission of the publisher.